2017 IEEE 26th International Symposium on Industrial Electronics (ISIE) 2017
DOI: 10.1109/isie.2017.8001435
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive self-organizing fuzzy logic controller in a serious game for motor impairment rehabilitation

Abstract: Rehabiliation robotics combined with video game technology provides a means of assisting in the rehabilitation of patients with neuromuscular disorders by performing various facilitation movements. The current work presents ReHabGame, a serious game using a fusion of implemented technologies that can be easily used by patients and therapists to assess and enhance sensorimotor performance and also increase the activities in the daily lives of patients. The game allows a player to control avatar movements throug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…An expanding number of analysts focus on portraying the estimation of rehabilitation intercessions that can be utilized all through the disease, from the underlying side effects to the propelled stages [4]. Our previous research [5], [6] have also shown that integrating off-the-shelf devices with video game rehabilitation program could facilitate a platform to enable…”
Section: Introductionmentioning
confidence: 99%
“…An expanding number of analysts focus on portraying the estimation of rehabilitation intercessions that can be utilized all through the disease, from the underlying side effects to the propelled stages [4]. Our previous research [5], [6] have also shown that integrating off-the-shelf devices with video game rehabilitation program could facilitate a platform to enable…”
Section: Introductionmentioning
confidence: 99%
“…Kinect seems to be the most preferred sensor for capturing body parts and following their movement in space, which was used by 15.4% (26/169) of the studies included in the review. Some of the studies used only the Kinect sensor for their systems [26,[62][63][64][65][66][67][68][69][70][71][72][73], whereas others combined it with biosignal capturing devices such as electromyogram (EMG) [24,41,74,75] or a sensing jacket [52] to gain better control of the user's movement for the final goal (ie, rehabilitation). In addition, some studies have used Kinect combined with gaming devices such as VR headsets [76] and a Wii balance board [77] or other devices such as goniometers [78][79][80], Tyromotion Timo plate [77], Xsen 3D sensor [81], body markers [82], and a customized haptic glove [83].…”
Section: Commercial Sensorsmentioning
confidence: 99%
“…A membership function µ A (x) associated with A is a function that maps X into [0, 1] and gives the grade of membership of X as A. The MF in the Vision Lab fuzzy logic system was triangular in the range of [0, 1] [19]. Eqn defines the triangular membership function.…”
Section: B Fuzzy Logic (Fl)mentioning
confidence: 99%